Argumentation and Reasoning Skills In Socioscientific Issues - Alindra, A. L.; Ana, Ana (INVOTEC, 2018)
Education is facing big challenges so that it can create qualify individuals in problem solving. Application of knowledge and or scientific concepts in the public is a realization of knowledge obtained by students at school. There are several ways to develop science education, one of which is through argumentation skill towards socioscientific issues. The socioscientific issue is scientific concept and problem-based issue, controversy, public discussion greatly influenced by socio-politics. This writing by literature study method aims to explore on argumentation skill for students so that they can face any problem solving challenges in daily life by studying; application of argumentation skill for socio scientific issue in daily life, argumentation and reasoning as well as Toulmin Argumentation Patter as the pattern used in student argumentation skill access.